FROM THE EXPERIENCE OF COLLECTING COMPROMISING TEXT OF THE HUSSAINI DEVONIAN - Djurayeva Buriyevna, Khusnigul; Djurayeva Buriyevna, Mokhigul (International Journal of Psychosocial Rehabilitation, 2020)
Hussein Baykhara, the famous statesman, has left an important mark as a poetic poet and antimuri commander who understands military tactics and strategy. During his reign, Hussein pays great attention to strengthening the state and improving economic, trade, cultural, scientific, and literary cooperation with neighboring countries. As a result, Khurasan has become the oldest city in the East with 32 craftsmen. In the manuscripts, it was noted that there were mosques and orphanages in the State of Hussein.Hussein Baykhara was a direct contributor to artistic creativity under the pseudonym "Hussein.". The legendary Uzbek writer, who was the author of the Turkish poetry, claimed that the heritage of the Uzbek language is not less than Persian. The poet's work was copied by famous writers of his time, such as Sultan Ali Mashhadî and Sultan Muhammad Handon. The article describes the manuscripts of Hussein's creative heritage kept in the funds of Uzbekistan and foreign countries. The copies of the book "Devoni Sultan Hussein Sayyid Mirza" are comparatively studied. Editorial copies of Baku, Istanbul, Kabul, and Tashkent related to Hussein's work are comparable, different, and similar. The Devon's T.I.1977 manuscript, which was being kept at the Istanbul University Library, was first introduced to the public. It was copied in the period of Hussein, and it was saved completely. Compared to other copies, it is relatively defectless and perfectly preserved. It was shaped as the book by the scribe Sultan Ali Mashhadî. This manuscript is a reference source. The collective and comparative text of the Hussein devon is a comprehensible imaginative of the poet's poetry, allowing for a consistent analysis of poetry in terms of the nature of the genre, the scope, the image system, and especially the artistic skill. Meanwhile, this manuscript was a base to create a composite and comparative text of the other poets of the fifteenth century.